Biological and mechanical measures for runoff and soil erosion control in India and beyond - Deepak Singh; Nisha Singh; Harendra Singh; Anita Kumawat; Pawan Jeet; Devideen Yadav; Anand K. Gupta; Gopal Kumar (Discover Applied Sciences)
Abstract Soil erosion poses a significant threat to agricultural sustainability, particularly in India, where approximately 83.0 million hectares of land are affected, with an average soil loss of 16.23 t ha−1 annually. This review systematically analyzes control practices for mitigating soil erosion in agricultural lands, focusing on their effectiveness in reducing runoff and soil loss. The findings highlight that biological methods, such as mulching and intercropping, are widely adopted, with mulching reducing soil loss and runoff by 5–18% and 3–15%, respectively. Tillage operations, particularly conservation tillage, have shown promise, reducing soil loss by 14–18% and improving infiltration rates. Mechanical methods, including contour bunds and terracing, further complement these efforts, achieving reductions in soil loss by 44–52% and runoff by 36–46%. The review underscores the importance of integrating biological and mechanical approaches for optimal erosion control, as well as the need for policy support and farmer education to promote widespread adoption. By addressing soil erosion through these practices, agricultural productivity, soil fertility, and environmental health can be significantly enhanced, contributing to global food security and sustainable land management goals.